The clinical efficacy and action mechanism of Bailing capsule in the treatment of microinflammatory and the condition of malnutrition in maintenance hemodialysis patients - HUANG Qiao; OUYANG Xu-ming; CHEN Wen-li (Linchuang shenzangbing zazhi)
Objective To investigate the clinical efficacy and action mechanism of Bailing capsule in the treatment of microinflammatory and the condition of malnutrition in maintenance hemodialysis(MHD)patients.Methods A total of 100 MHD patients who were treated in the Hemodialysis Center of Wuhan Central Hospital from March 2016 to September 2016 were enrolled in the study and randomly divided into two groups.Among them,there were 58 males and42 females,aged29 to70 years,with an average of(45.6±12.4)years.All patients were clinically judged to have dry weight and given long-term pathway establishment.All patients did not take bailing capsules,glucocorticoids and compound a-ketoacid tablets within 3 months before the start of the study.There was no statistically significant difference between the two groups in terms of sex,age,pathogenesis,hemodialysis mode and anemia.In the control group,MHD was given,blood pressure was controlled,anemia and the disorders of calcium-phosphate metabolism corrected,and symptomatic supportive treatment done.In the treatment group,patients were given Bailing capsule(1.0 g,thrice every day)additionally.Changes in hs-CRP,TNF-α,IL-6,Alb,PA,TC and nutritional status were observed before and after treatment in the two groups.Results The hs-CRP,TNF-αand IL-6 levels were decreased significantly in the two groups after the treatment(P <0.05),more significantly in the treatment group than in the control group(P<0.05).MQSGA was markedly improved in the treatment group as compared with the control group(P<0.05).There was no statistically significant difference between the two groups in terms of Alb and TC after treatment.Conclusions Bailing capsule can improve microinflammatory and the condition of malnutrition in MHD patients,probably by reducing anti-inflammatory factors and promoting the protein synthesis and use of amino acids.